Affordability and the political economy of social protection in contemporary Africa - Jeremy Seekings (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The 'affordability' of new or expanded social protection programmes depends on more than an assessment of the fiscal costs or the poverty-reducing or developmental benefits. Diverse international organizations have shown that programmes costing less than or about 1 per cent of GDP have substantial benefits, and most low-income countries have the 'fiscal space' for such programmes (including through increased taxation). These international organizations have generally failed to convince national policy-making elites to raise and to allocate scarce domestic resources to social protection programmes. The result is an 'affordability gap' between what is advocated for African countries and what these countries' governments are willing to spend. This paper examines four cases of contestation over the 'affordability' of social protection reforms in Africa: Botswana, South Africa, Zambia, and the semi-autonomous territory of Zanzibar. In all four cases, political elites have resisted or rejected proposals for expensive reforms, and the most expensive reforms adopted cost only 0.4 to 0.5 per cent of GDP. The governments of Zambia and Botswana generally resisted even expenditures of this magnitude. The cost ceiling for reforms is far below the estimates of international organizations, reflecting political, normative and ideological factors.
Keywords: I38; O29; O57; O21; 330; social protection; fiscal space; social spending